PENGARUH KOMPENSASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Tetap PT Citra Sigma Kertaswara Indonesia) - Rikha, Salsa Rikha; Oktaviar, Chairiel (Journal of Fundamental Management (JFM), 2024)
This study aims to analyze the effect of compensation, motivation and workenvironment on the performance of permanent employees at PT. Citra Sigma Kertaswara Indonesia. The population in this study is permanent employees of PT. Citra Sigma Kertaswara Indonesia as many as 40 peoples using a quantitative approach and using saturated sample techniques for determining sample size. The data collection method uses a survey method with questionnaires as research instruments. The approach used is the Structural Equation Model (SEM) with Smart-PLS analysis. The results of this study prove that compensation has a positive and significant effect on employee performance, motivation has a positive insignificant effect on employee performanceand the work environment has a positive and significanteffect on employee performance.